Art, Music and Religious Experience in Libation Pouring of Akan Religion - Ayim-Aboagye, Desmond (Scripta Instituti Donneriani Aboensis, 1996)
The Akans of Ghana are traditionally accustomed to celebrating different rituals which are enshrined in their cultural life. Libation pouring, which accompanies the celebration of great rituals, amidst the subsidence of the sound of music and dance, can display a special art in religion. The primary objective of this paper is to examine libation as a ritual experience, and in so doing to draw attention to its art forms and relevance as regards the psychological significance for the Akan society which practises it. What beliefs connect the pouring of libation in Akan society? What are the occasions for practising this ritual? Are there some distinctions in the artistic prayer of libation? These questions lead directly to the proposition which states that libation is able to generate some forms of religious experience. It is then argued that libation ritual has psychological consequences beneficial to the group and the individual who privately engages in it.